The influence of the Determinants and Generation Type on Intention to Retire - Wen Huey, Kan; Muthuveloo, Rajendran (Journal of Entrepreneurship, Business and Economics; Vol 7 No 2s (2019): Special Issue: Contemporary Business Issues in Malaysia: How does this “Tiger Cub” feel today?, 2019)
This is a proactive study to assist the Malaysian Ministry of Education to understand better about factors that associated with the determinants of early retirement among government female secondary school teachers. This paper illustrates the determinants of intention to retire among government female secondary school teachers. These determinants were chosen based on the three faculty of human beings called physical, mental and spiritual. Health and Financial resources represent the physical and mental aspects respectively, while job satisfaction and work performance represent the spiritual aspect. In addition, it elaborates the influence of generation type on the relationship between the determinants and the intention to retire. Two hundred and ninety-two (292) samples were collected using structured questionnaire via convenience sampling technique and analysed with SPSS and PLS-SEM statistical tools. The results indicated that health, financial resource and work performance forms the determinants of intention to retire, while job satisfaction do not. Generation type moderates the relationship between the determinants and intention to retire. These findings provide a proxy of early retirement of the teacher from the job or leaves the job elsewhere for better prospect. This study can be the benchmark for the Malaysian Government-Ministry of Education to address the shortage of manpower at the secondary school level. In addition, the strategic insights and practical knowledge provided by this study can assist the Malaysian Government-Ministry of Education to formulate strategies to manage shortage of teacher at the secondary school and increase to labor force participation of women. Research paper  Keywords: Intention to Retire; Health; Financial Resources; Job Satisfaction; Work Performance; Generation Type Reference to this paper should be made as follows: Wen Huey, K., & Muthuveloo, R. (2019). The influence of the Determinants and Generation Type on Intention to Retire: A Study Among Government Female Secondary School Teachers., Journal of Entrepreneurship, Business and Economics , 7 (2s), 7–41.